The effect of conventional mechanical periodontal treatment on red complex microorganisms and clinical parameters in Down syndrome periodontitis patients: a pilot study - Tanaka, Marcia Hiromi [UNESP]; Rodrigues, Thamiris Orrico [UNESP]; Finoti, L. S. [UNESP]; Teixeira, S. R. L.; Mayer, M. P. A.; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Giro, Elisa Maria Aparecida [UNESP] (Springer Nature, 2014)
Periodontal disease (PD) is induced by a complex microbiota, such as Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola (together called the red complex), which triggers intense inflammatory reaction. Down syndrome (DS) individuals demonstrate a high prevalence of PD compared with those who are otherwise chromosomally normal (euploids). This pilot study aimed to evaluate the effect of non-surgical periodontal treatment in DS chronic periodontitis patients on clinical and microbiological parameters. Patients with chronic periodontitis, 23 DS and 12 euploids (control group), were submitted to non-surgical mechanical periodontal treatment, followed by maintenance for 45 days. Clinical parameters after periodontal treatment were similar in diseased and healthy sites, independent of the genetic background. Diseased sites of DS and control patients harbored similar levels of P. gingivalis and T. forsythia at baseline, but significantly higher levels of T. denticola were found in DS patients. Increased levels of P. gingivalis at healthy sites were found in DS individuals. Non-surgical periodontal therapy decreased the levels of red complex microorganisms and improved the tested clinical parameters of diseased sites in both groups. However, the levels of red complex bacteria were higher in diseased sites of DS patients after the periodontal treatment. We conclude in this pilot study that, although the mechanical periodontal treatment seemed to be effective in DS subjects over a short-term period, the red complex bacteria levels did not decrease significantly in diseased sites, as occurred in controls. Therefore, for DS patients, it seems that the conventional non-surgical periodontal therapy should be improved by utilizing adjuvants to reduce the presence of periodontopathogens.